It is currently 02 Apr 2020, 01:54
My Tests

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

If 6x - 4y = 2 and x = 3, then x + y =

  Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:
Founder
Founder
User avatar
Joined: 18 Apr 2015
Posts: 10110
Followers: 209

Kudos [?]: 2504 [0], given: 9501

CAT Tests
If 6x - 4y = 2 and x = 3, then x + y = [#permalink] New post 16 Mar 2020, 09:40
Expert's post
00:00

Question Stats:

100% (00:23) correct 0% (00:00) wrong based on 5 sessions
If \(6x - 4y = 2\) and \(x = 3\), then \(x + y = \)

(A) 4

(B) 5

(C) 7

(D) 12

(E) 19


Kudos for the right answer and explanation
[Reveal] Spoiler: OA

_________________

Need Practice? 20 Free GRE Quant Tests available for free with 20 Kudos
GRE Prep Club Members of the Month: Each member of the month will get three months free access of GRE Prep Club tests.

1 KUDOS received
GRE Instructor
User avatar
Joined: 10 Apr 2015
Posts: 2954
Followers: 110

Kudos [?]: 3260 [1] , given: 55

CAT Tests
Re: If 6x - 4y = 2 and x = 3, then x + y = [#permalink] New post 25 Mar 2020, 07:02
1
This post received
KUDOS
Expert's post
Carcass wrote:
If \(6x - 4y = 2\) and \(x = 3\), then \(x + y = \)

(A) 4
(B) 5
(C) 7
(D) 12
(E) 19


Given: \(6x - 4y = 2\)
Since we're also told that \(x = 3\), we can substitute this information into the given equation to get: \(6(3) - 4y = 2\)
Simplify to get: \(18 - 4y = 2\)
Subtract \(18\) from both sides to get: \(-4y = -16\)
Divide both sides by \(-4\) to get: \(y = 4\)

Now that we know that \(x = 3\) and \(y = 4\), we also know that \(x + y = 3 + 4 = 7\)

Answer: C

Cheers,
Brent
_________________

Brent Hanneson – Creator of greenlighttestprep.com
Sign up for my free GRE Question of the Day emails
Image

Re: If 6x - 4y = 2 and x = 3, then x + y =   [#permalink] 25 Mar 2020, 07:02
Display posts from previous: Sort by

If 6x - 4y = 2 and x = 3, then x + y =

  Question banks Downloads My Bookmarks Reviews Important topics  


GRE Prep Club Forum Home| About| Terms and Conditions and Privacy Policy| GRE Prep Club Rules| Contact

Powered by phpBB © phpBB Group

Kindly note that the GRE® test is a registered trademark of the Educational Testing Service®, and this site has neither been reviewed nor endorsed by ETS®.